Comparative transcriptome and proteome analysis of resistant and susceptible Talaromyces marneffei clinical isolates reveals a systemic multitiered defense network against azoles - Zheng Yanqing; Peng Gaoyuan; Pang Xiaofeng; Liang Chaojuan; Luo Xiaolu; Wei Cailing; Qin Jianglong; Zou Jun; Wang Zhiyi; Pan Kaisu; Du Mingwei; Xue Peng; et al. (Antimicrobial Agents and Chemotherapy, 2026)
ABSTRACT Talaromyces marneffei is a thermally dimorphic fungus causing life-threatening systemic mycosis in immunocompromised patients. The emergence of azole-resistant clinical isolates, especially those with reduced susceptibility to voriconazole (VOC) and fluconazole (FLC), presents a critical therapeutic challenge. Although target-gene alterations and efflux-related mechanisms have been reported in pathogenic fungi, the broader molecular basis distinguishing high-minimum-inhibitory concentration (MIC) and low-MIC T. marneffei clinical isolates remains incompletely defined. Here, we performed integrated transcriptomic (RNA-seq), proteomic (DIA-LC-MS/MS), and RT-qPCR analyses comparing four resistant and four susceptible T. marneffei clinical isolates. Differentially expressed genes and proteins were identified, functionally interpreted, and integrated to prioritize resistance-associated molecular candidates. The multi-omics results supported a constitutive, multitiered resistance-associated state involving transport and cell wall processes, redox-detoxification, mitochondrial metabolism, and stress regulatory adaptation. Signals involving coilin, CatA, and other discriminant features contributed to the multi-omics prioritization layer. RT-qPCR supported a 17-gene panel associated with transport, redox-detoxification, mitochondrial metabolism, and stress regulation. Five genes, PMAA_008970 , PMAA_058960 , PMAA_070510 , PMAA_088690 , and PMAA_092180 , showed statistically significant R/S differences, while the remaining panel members were detectable and trend-supporting within the same functional framework. These findings refine a hierarchical azole-resistance model in T. marneffei and provide a focused candidate panel for future mechanistic validation.